Measuring Chilli Farmer Satisfaction to Improve the Quality of Jacko 99 Brand Seeds - Yekti, Ananti; Safitri, Ipah Mardiyana Nur (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2025)
Understanding and categorizing product attributes can help design products that meet consumer needs and preferences, leading to higher satisfaction and loyalty. This study aims to (1) find out the characteristics of farmers who use Jacko 99 brand chilli seed in Magelang Regency, (2) analyze the perception of farmers on the level of importance and performance of Jacko 99 brand chilli seed attributes in Magelang Regency, and (3) measure the level of satisfaction of Jacko 99 brand chilli farmers in Magelang Regency. Research activities were carried out from April to December 2024. This research is descriptive research with quantitative analysis. The research sample comprised 60 respondents, determined by non-probability sampling from the population of Jacko 99-brand chilli farmers in Magelang Regency. The results of the Importance Performance Analysis show that two attributes must be improved: resistance to pest diseases and the freshness and durability of chilli. The results of the Customer Satisfaction Index showed that consumers of Jacko 99-brand chilli seeds were very satisfied, with a satisfaction index value of 86.14% (0.86). It is recommended to the producer of the Jacko 99 brand chilli seed to improve the resistance to pest diseases, durability of fresh chilli fruit, and also maintain the achievements of attributes that have already given satisfaction to the chilli farmers.